2009
DOI: 10.1088/0004-6256/139/1/120
|View full text |Cite
|
Sign up to set email alerts
|

THE CARNEGIE SUPERNOVA PROJECT: ANALYSIS OF THE FIRST SAMPLE OF LOW-REDSHIFT TYPE-Ia SUPERNOVAE

Abstract: An analysis of the first set of low-redshift (z<0.08) Type Ia supernovae monitored by the Carnegie Supernova Project between 2004 and 2006 is presented. The data consist of well-sampled, high-precision optical (ugriBV ) and near-infrared (NIR; Y JHK s ) light curves in a well-understood photometric system. Methods are described for deriving light-curve parameters, and for building template light curves which are used to fit Type Ia supernova data in the ugriBV Y JH bands. The intrinsic colors at maximum light … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
276
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 328 publications
(303 citation statements)
references
References 79 publications
(106 reference statements)
22
276
5
Order By: Relevance
“…There have also been several studies on this subject using SNe Ia. Most recently, Folatelli et al (2010) solved for R V in the same manner as our approach (i.e., by minimizing the dispersion in the HD) and obtained a value of R V ≈ 1.5, remarkably consistent with our value. Further evidence for low R λ values using SNe Ia were reported by others applying a similar procedure (Phillips et al 1999;Altavilla et al 2004;Reindl et al 2005;Hicken et al 2009;Wang et al 2009).…”
Section: Variations Of the Extinction Lawsupporting
confidence: 84%
“…There have also been several studies on this subject using SNe Ia. Most recently, Folatelli et al (2010) solved for R V in the same manner as our approach (i.e., by minimizing the dispersion in the HD) and obtained a value of R V ≈ 1.5, remarkably consistent with our value. Further evidence for low R λ values using SNe Ia were reported by others applying a similar procedure (Phillips et al 1999;Altavilla et al 2004;Reindl et al 2005;Hicken et al 2009;Wang et al 2009).…”
Section: Variations Of the Extinction Lawsupporting
confidence: 84%
“…With these corrections, the dispersion in well measured optical band peak magnitudes is only ∼ 0.12 magnitudes (Hicken et al 2009b;Folatelli et al 2010), allowing each well measured supernova to provide a luminosity-distance estimate with ∼ 6% uncertainty. The diversity of SN Ia light curves is not fully understood, and peculiar SNe Ia appear to produce ∼ 5% non-Gaussian tails in the SN Ia distribution .…”
Section: General Principlesmentioning
confidence: 99%
“…Analysis by Pskovskii (1984), followed by Phillips (1993), established a correlation between the magnitude of a SN Ia at peak brightness and the rate at which it declines, thus allowing supernova luminosities to be "standardized". This method currently probes farthest into the unperturbed Hubble flow, and it possesses very low intrinsic scatter: in recent studies, the decline-rate corrected SN Ia Hubble diagram is found to have a dispersion of ±7-10% in distance (e.g., Folatelli et al 2009, Hicken et al 2009). …”
Section: Type Ia Supernovaementioning
confidence: 99%